Recovery of Fatty Acid and Volatile Flavor Compound Composition in Farmed Tiger Puffer (Takifugu rubripes) with a Fish Oil-Finishing Strategy - Lin Li; Feiran Zhang; Xiaoxue Meng; Xishuai Cui; Qiang Ma; Yuliang Wei; Mengqing Liang; Houguo Xu (Marine Drugs, 2023)
Booming fish farming results in a relative shortage of fish oil (FO) supply, meaning that alternative oils are increasingly used in fish feeds, which leads to reduction of long-chain polyunsaturated fatty acids (LC-PUFAs) and other relevant changes in fish products. This study investigated the efficacy of an FO-finishing strategy in recovering the muscle quality of farmed tiger puffer. An eight-week feeding trial (growing-out period) was conducted with five experimental diets, in which graded levels (0 (control), 25, 50, 75, and 100%) of added FO were replaced by poultry oil (PO). Following the growing-out period was a four-week FO-finishing period, during which fish in all groups were fed the control diet. Dietary PO significantly decreased the muscle LC-PUFA content, whereas in general, the FO-finishing strategy recovered it to a level comparable with that of the group fed FO continuously. The recovery efficiency of EPA was higher than that of DHA. Dietary PO also led to changes of volatile flavor compounds in the muscle, such as butanol, pentenal, and hexenal, whereas the FO-finishing strategy mitigated the changes. In conclusion, the FO-finishing strategy is promising in recovering the LC-PUFA and volatile-flavor-compound composition in farmed tiger puffer after the feeding of PO-based diets.